2005
DOI: 10.1038/sj.onc.1208902
|View full text |Cite
|
Sign up to set email alerts
|

Mutations of tumor necrosis factor α-responsive serine residues within the C-terminal transactivation domain of human transcription factor REL enhance its in vitro transforming ability

Abstract: The human c-rel gene (REL), encoding an NF-kappaB transcription factor, is amplified or mutated in several human B-cell lymphomas and can transform chicken lymphoid cells in vitro. We have previously shown that certain deletions of C-terminal transactivation sequences enhance REL's transforming ability in chicken spleen cells. In this report, we have analysed the effect of single amino-acid changes at select serine residues in the C-terminal transactivation domain on REL's transforming ability. Mutation of eit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(54 citation statements)
references
References 41 publications
2
52
0
Order By: Relevance
“…We have recently shown that mutations at Ser460 or Ser471, which enhance REL's transforming ability, also affect MnSOD expression in opposite ways in A293 cells versus chicken spleen cells (Starczynowski et al, 2005). As discussed therein, the differences in MnSOD expression in transient transfection experiments in A293 cells versus in stably transformed chicken spleen cells may reflect the kinetics of REL-induced gene expression.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We have recently shown that mutations at Ser460 or Ser471, which enhance REL's transforming ability, also affect MnSOD expression in opposite ways in A293 cells versus chicken spleen cells (Starczynowski et al, 2005). As discussed therein, the differences in MnSOD expression in transient transfection experiments in A293 cells versus in stably transformed chicken spleen cells may reflect the kinetics of REL-induced gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…As a control, we also measured MnSOD protein levels in cells expressing REL-S533,536A, a mutant that behaves similarly to wild-type REL in transformation and transactivation assays (Martin et al, 2001;Starczynowski et al, 2005). The level of MnSOD protein in A293 cells overexpressing REL-S525P was approximately 4.5-fold higher than in cells transfected with the vector control, whereas the levels of MnSOD protein in cells overexpressing wild-type REL or REL-S533,536A were approximately 7.5-fold higher than in control cells ( Figure 5a).…”
Section: Rel-s525p Has Enhanced Transforming Ability In Chicken Spleementioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, in one of the lymphoma patients the S525P mutation is a germline mutation, suggesting that this alteration could be a predisposing mutation for lymphoma. It would not be surprising if other human B-cell lymphomas, with or without REL gene amplification, have activating mutations in REL, especially given that a variety of point mutations and deletions within the REL transactivation domain can enhance the in vitro transforming activity of REL (Starczynowski et al, 2003(Starczynowski et al, , 2005.…”
Section: Multiple Familial Trichoepitheliomamentioning
confidence: 99%